EFEKTIVITAS PENGGUNAAN MEDIA KARTU HURUF DAN KARTU KATA BERGAMBAR TERHADAP KEMAMPUAN MEMBACA PERMULAAN PADA SISWA KELAS I SD NEGERI 228 LAGAROANG KEC. MALILI KAB. LUWU TIMUR - Syarif, Anindya Fiska; Ilyas; Halimah, Andi (Primer Edukasi Journal, 2024)
This thesis discusses 1) How is the reading ability of class I students at SD Negeri 228 Lagaroang taught using letter cards media, 2) How is the reading ability of class I students at SD Negeri 228 Lagaroang taught using picture word cards media, 3) Is there a difference Beginning reading skills taught using letter card media and using picture word card media to students at SD Negeri 228 Lagaroang. The purpose of this study was to determine (1) the initial reading ability of class I students at SD Negeri 228 Lagaroang who were taught using letter cards as media, (2) the initial reading ability of class I students at SD Negeri 228 Lagaroang who were taught using picture word cards as media and (3 ) differences in initial reading ability between those taught using letter card media and picture word card media in class I students of SD Negeri 228 Lagaroang. This type of quasi-experimental research (quasi-experimental) uses a pretest-posttest nonequivalent control group design. The population is class I SD Negeri 228 Lagaroang, Malili District, East Luwu Regency, which consists of 3 classes of 69 people. The sampling technique used was a multi-stage sampling technique so that 2 classes of 40 students were selected. The instrument used in this study is a test. Data were analyzed using descriptive statistical analysis and inferential statistical analysis. The results of the descriptive analysis showed that for class IA, the average score before being given treatment (pretest) was 40.25 and the average value after being given treatment (posttest) was 81.25. Whereas in class IB, the average score before being given treatment (pretest) was 40.5 and the average value after being given treatment (posttest) was 73.75. Based on the results of the SPSS analysis, a significant value was obtained α (0.028 <0.05). Thus the researchers concluded that there was a difference in the average initial reading ability scores of students who were taught using letter cards media and those taught using picture word cards media in class I SD Negeri 228 Lagaroang, Malili District, East Luwu Regency. The implication of this study is to show that the letter card media is higher than the picture word card media on students' reading abilities. However, these two media are equally effective and have increased students' reading skills after using these two media and from this research it can be used as a consideration for teachers to be able to design letter card media and picture word card media in order to improve students' reading skills.